Analisis Sistem Pengendalian Internal Atas Pelaksanaan Dana Operasional Sekolah (BOS) Pada Dinas Pendidikan Kota Mataram - Wijaya, Gede Krisna Ananta Wijaya; Suhaedi, Wirawan; Waskito, Iman (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to determine the analysis of the internal control system for the implementation of school operational funds (BOS) at the Mataram City education office. This type of research is qualitative descriptive research. This research was conducted under the auspices of the Mataram City Education Department in 4 junior high schools, namely SMPN 15 MATARAM, SMPN 16 MATARAM, SMPN 9 MATARAM, and SMPN 7 MATARAM. Data collection techniques are in the form of interviews, observation and documentation. The results of this research show that the analysis of the internal control system for the implementation of school operational funds (BOS) at the Mataram City Education Department as a whole can be said to be that the internal control system in 4 schools (SMP) is quite effective and efficient. The implementation of the Boss’s funds is in accordance with the Boss’s Technical Guidelines regulations.